2013
DOI: 10.1002/chem.201301991
|View full text |Cite
|
Sign up to set email alerts
|

A Flexible Approach to Strained Sandwich Compounds: Chiral [1]Ferrocenophanes with Boron, Gallium, Silicon, and Tin in Bridging Positions

Abstract: The enantiomerically pure dibromoferrocene 3 [(Sp,Sp )-1,1'-dibromo-2,2'-di(isopropyl)ferrocene], equipped with two iPr groups in α positions, was prepared using known "Ugi amine" chemistry. Species 3 was targeted in order to gain access to new [1]ferrocenophanes ([1]FCPs) to be used as monomers for ring-opening polymerization. The iPr groups on the sandwich unit were introduced to stabilize bridging moieties, as well as to increase solubilities of targeted metallopolymers. The planar chiral dibromide 3 can qu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
95
0

Year Published

2014
2014
2017
2017

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 30 publications
(98 citation statements)
references
References 80 publications
3
95
0
Order By: Relevance
“…As expected, the molecular structure of 3 3-Pen did not reveal any surprises. Its structure is very similar to that of 3 iPr , [11] including the conformation of the alkyl groups, a fact that will become important for the later discussion (see mechanistic insights below). Both dibromides, 3 iPr and 3…”
Section: Resultsmentioning
confidence: 88%
See 4 more Smart Citations
“…As expected, the molecular structure of 3 3-Pen did not reveal any surprises. Its structure is very similar to that of 3 iPr , [11] including the conformation of the alkyl groups, a fact that will become important for the later discussion (see mechanistic insights below). Both dibromides, 3 iPr and 3…”
Section: Resultsmentioning
confidence: 88%
“…Recently, we had shown that addition of 2.1 equivalents of nBuLi to 3 iPr in a solvent mixture of thf/hexanes (1:9) results in a clean lithium-bromide exchange (Scheme 1); [11,19] . It seems that the lack of formation of crystals of the latter two species prohibited further purification. )…”
Section: -Penmentioning
confidence: 99%
See 3 more Smart Citations